Reconstructing Public Accountability in Evidence Management within Law Enforcement Institutions - Wawan Setiawan; Andries Lionardo; Alfitri; Slamet Widodo (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
This study examines the reconstruction of public accountability in evidence management within law enforcement institutions through a relational–systemic governance perspective. The study employs a qualitative case study approach conducted at the Public Prosecutor’s Office of Palembang. Data were collected through in-depth interviews, observation, and document analysis involving prosecutors, evidence officers, administrative personnel, and institutional supervisors directly engaged in evidence management processes. The analysis focused on four principal accountability dimensions consisting of actors, objects, forums, and interaction mechanisms. The results reveal that accountability practices in evidence management remain predominantly procedural, hierarchical, and compliance-oriented. Accountability mechanisms mainly emphasize administrative reporting, inventory control, and procedural conformity, while broader dimensions such as transparency, public trust, collaborative governance, responsiveness, and organizational learning have not yet been optimally integrated. The findings further show that fragmented coordination among institutional actors, limited participatory accountability forums, and rigid bureaucratic communication mechanisms weaken accountability effectiveness and reduce institutional adaptability. This study develops the Relational–Systemic Accountability Model Based on Public Service (ARS–PP Model), which integrates collaborative institutional responsibility, public value orientation, participatory accountability forums, and adaptive interaction mechanisms into a unified accountability framework. The findings suggest that accountability effectiveness in evidence management depends on institutional integration, collaborative governance capacity, adaptive coordination systems, and public-oriented governance transformation.